Increasing Volcanic Eruption Disaster Mitigation Through Simulation Practice with Video Learning Media in Geography Education, University of Khairun - Lely Adriani Nasution; Andi Tenri Pada Agustang; Johan Maulana (Universitas Lambung Mangkurat, 2023)
The volcanic eruption disaster is the most potential disaster in Ternate. When PVMBG published the press release on May, 3rd , 2023, it raised concerns for the society. Therefore, to built an awareness and information about volcanic eruption, it is necessary to give the knowledge from the school level to the university level. This research aims to analyze and describe the application of theory to disaster mitigation courses at Geography Education Study Program, University of Khairun. The method in this researh is using a Pre-experimental Research with One Group Pretest-Posttest Design through of using video learning media. The result showed that the use of video learning media was able to increase students understanding of volcanic eruption disaster mitigation, and also increasing skill in practicing volcanic eruption disaster mitigation simulation.